TRANSFORMATION OF ELEMENTARY EDUCATION ARCHIVES: PERCEPTIONS AND EXPERIENCES OF THE ADMINISTRATIVE STAFF OF ANNYSA PRIVATE ELEMENTARY SCHOOL IN USING DIGITAL AND MANUAL ARCHIVE SYSTEMS - Shinta, Dewi; Prd, Intan Amalia Putri; Ramadhani, Jihan Aulia; Abdillah, Mhd Rizki; Mardiah, Raudhatul; Sembiring, Ummi Auliyah (REKOGNISI : Jurnal Pendidikan dan Kependidikan (E-ISSN 2599-2260), 2025)
Every organization, be it a government agency, private institution or educational institution such as elementary school, must have administrative activities that are the basis for running daily operations. Administration related to correspondence or archiving of important documents belonging to the school or office. In the digital era, many agencies and schools have begun to switch from manual archive systems to digital archive systems. However, not all schools or offices have implemented the digitalization system optimally. Agencies or schools that have switched or implemented this digital archive system must have their own experiences and perceptions regarding this digital archive system. And of course they already know the advantages and disadvantages of both archive systems.